Cassava in focus: A comprehensive literature review, its production, processing landscape, and multi-dimensional benefits to society - Abraham Woru Borku; Thomas Toma Tora; Mamush Masha (Food Chemistry Advances)
Cassava (Manihot esculenta Crantz), an underutilized yet adaptable crop, holds significant potential to enhance food security, livelihood, and economic development for rural communities of developing countries. This review explores cassava's production, processing, and contributions in Africa, focusing on Ethiopia. Despite its resilience to climate variability and ability to grow in marginal soils, cassava remains underutilized compared to its extensive use in other African countries. A comprehensive literature review methodology was employed, critically evaluating studies. Cassava processing remains rudimentary, relying on small-scale, labor-intensive methods, with inefficient technologies posing risks to consumer health from improperly processed products. However, cassava provides socio-economic benefits for smallholder farmers by diversifying income, creating employment, and reducing vulnerability to shocks. Nutritionally, cassava is a calorie-rich energy source for food-insecure households, but improper processing can cause health risks such as cyanide poisoning. This review highlights the urgent need for multi-sectoral collaboration among policymakers, researchers, extension services, and private actors to unlock cassava's potential. Key actions include developing improved varieties, enhancing value chains, promoting public-private partnerships, and raising awareness about safe processing. A comprehensive evaluation of cassava's production, processing, and utilization is essential to optimize its role as a sustainable food source in Ethiopia.